CYBER TERRORISM PREVENTION AND ERADICATION IN INDONESIA AND ROLE AND FUNCTIONS OF MEDIA - Makarim, Edmon (Indonesian Journal of International Law, 2021)
The objective of terrorist is to create widespread fear to the society. This issue has then direct or indirect influent to the role of print and electronic media. Nowadays, the terrorist acts are carried out not only with physical violence but also by non-physical means through the medium of internet as a global communication. The main question is, whether terror groups could be protected as part of the freedom of expression. This article discusses mainly on the prevention and eradication of cyber terrorism in Indonesia and its relations to the role and function of Media.